Use of Complementary and Alternative Medicine and Adherence to Medication Therapy Among Stroke Patients: A Meta-analysis and Systematic Review - Rajahthurai, Sareneya Dashni; Farrukh, Muhammad Junaid; Makmor-Bakry, Mohd; Tan, Hui Jan; Fatokun, Omotayo; Mohd Saffian, Shamin; Ramatillah, Diana Laila (Frontiers in Pharmacology, 2022)
Purpose: To identify the use patterns of complementary and alternative medicine (CAM) and its impact on medication adherence among patients with stroke. Method: A systematic search through Science Direct, Google Scholar, and PubMed was performed to identify potential studies up to June 2021.The primary outcome was CAM use, and the secondary outcome was medication adherence among patients with stroke. Articles included in the review met the following criteria: (1) stroke patient aged 18 years and above, (2) on prescribed medications, and (3) reported status of adherence to medications. Meta-analyses were conducted to estimate the pooled prevalence of complementary and alternative medicine and adherence in stroke patients using a random-effects model. Results: A total of 1,330 studies were screened, of which 22 were included in the final analysis. The pooled prevalence of CAM usage was at 38% (29-48% CI) and medication non-adherence among stroke patients was at 29% (20-48% CI). The most common reason for inadequate stroke therapy and higher dependence on CAM was the patients’ lack of knowledge and the regimen complexity of the medication. Other factors for medication non-adherence were forgetfulness, side effects, cost, and lack of doctor-patient communication. Conclusion: A low prevalence of CAM usage and non-adherence to medications was observed among patients with stroke. Studies investigating the association between CAM usage and medication adherence among patients with stroke are scarce and future research is needed to explore the influence of CAM use on stroke medication adherence.